A Case of Autosomal Dominant Osteopetrosis Type 2 with a CLCN7 Gene Mutation - Sol Kang; Young Kyung Kang; Jun Ah Lee; Dong Ho Kim; Jung Sub Lim (Galenos Yayincilik, 2019)
Osteopetrosis is a rare genetic disease characterized by increased bone density and bone fractures due to defective osteoclast function. Autosomal dominant osteopetrosis type 2 (ADO-2), Albers-Schonberg disease, is characterized by the sclerosis of bones, predominantly involving the spine, pelvis and the base of the skull. Here, we report a typical case of osteopetrosis in a 17.7-year-old male who carries a heterozygous c.746C>T mutation in exon 9 in the chloride voltage-gated channel 7 (CLCN7) gene. The patient's spine showed multiple sclerotic changes including sandwich vertebra. His father had the same mutation but his skeletal radiographs were normal. This is the first reported case of ADO-2, confirmed by genetic testing in a Korean patient.